Multi-degree cyclic flow shop robotic cell scheduling problem with multiple robots. Issue 8 (3rd August 2017) - Elmi, Atabak; Topaloglu, Seyda
Abstract : This paper deals with the cyclic flow shop robotic cell scheduling problem with multiple robots, in which parts are processed successively on multiple machines with lower and upper bounds on processing times and the robots execute the transportation of parts between the machines. A novel mixed-integer linear programming model has been proposed for this problem. The proposed model simultaneously determines the optimal degree of the cyclic schedule and the optimal sequencing of the robots moves, which in return maximises the throughput rate. The validity of the proposed model is examined by a computational study on a set of randomly generated problem instances and solved using commercial optimisation software GAMS. The computational experiments indicate the efficiency of proposed model.